When the Casimir energy is not a sum of zero-point energies - De Albuquerque, Luiz C. [UNESP]; Cavalcanti, R. M. (American Physical Society (APS), 2002)
We compute the leading radiative correction to the Casimir force between two parallel plates in the λΦ4 theory. Dirichlet and periodic boundary conditions are considered. A heuristic approach, in which the Casimir energy is computed as the sum of one-loop corrected zero-point energies, is shown to yield incorrect results, but we show how to amend it. The technique is then used in the case of periodic boundary conditions to construct a perturbative expansion which is free of infrared singularities in the massless limit. In this case we also compute the next-to-leading order radiative correction, which turns out to be proportional to λ3/2. © 2002 The American Physical Society.